2022
DOI: 10.1007/s40618-022-01906-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nuclear autoantibodies in Graves’ disease and Graves’ orbitopathy

Abstract: Objective A relationship between thyroid and non-organ-specific autoimmunity could be relevant for Graves’ orbitopathy (GO), which affects connective tissue. We investigated the association between GO and anti-nuclear antibodies (ANAs). Methods Retrospective investigation was conducted in 265 patients with Graves’ disease (GD), 158 with and 107 without GO. Primary outcome was: prevalence of ANAs in GO vs no-GO. Secondary outcomes were: (1) relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…ANA positivity is a risk factor for thyroid autoimmunity. However, as shown by G. Lanzolla et al., being ANA positive protected against the development of Graves’ disease and reduced its severity ( 29 ). The study of ANA patterns is of tremendous interest in the fields of immunology and rheumatology since distinct patterns may have diverse clinical, diagnostic, and prognostic implications.…”
Section: Discussionmentioning
confidence: 97%
“…ANA positivity is a risk factor for thyroid autoimmunity. However, as shown by G. Lanzolla et al., being ANA positive protected against the development of Graves’ disease and reduced its severity ( 29 ). The study of ANA patterns is of tremendous interest in the fields of immunology and rheumatology since distinct patterns may have diverse clinical, diagnostic, and prognostic implications.…”
Section: Discussionmentioning
confidence: 97%
“…indicated that the presence of antinuclear antibodies was observed in around 80% of patients diagnosed with GD. This finding suggested that GD may potentially influence the development of SLE through the autoantibody pathway ( 40 ). Furthermore, a shared immunological pathway in the development of SLE and GD is suggested by the overlapping presence of specific chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…An Italy retrospective investigation was conducted the ANA positivity rate arrived 80% in 265 patients with GD ( 25 ). Another Italy research assessed the prevalence of ANA in 96 pediatric patients with AITD, in which 86 children with chronic lymphocytic thyroiditis and 7 with GD, the ANA positivity was 71% ( 26 ).…”
Section: Discussionmentioning
confidence: 99%